The Global Nutrition Report 2014: Actions and Accountability to Accelerate the World's Progress on Nutrition. Issue 4 (4th March 2015) - Haddad, Lawrence; Achadi, Endang; Bendech, Mohamed Ag; Ahuja, Arti; Bhatia, Komal; Bhutta, Zulfiqar; Blössner, Monika; Borghi, Elaine; Colecraft, Esi; de Onis, Mercedes; Eriksen, Kamilla; Fanzo, Jessica; et al.
Abstract: In 2013, the Nutrition for Growth Summit called for a Global Nutrition Report (GNR) to strengthen accountability in nutrition so that progress in reducing malnutrition could be accelerated. This article summarizes the results of the first GNR. By focusing on undernutrition and overweight, the GNR puts malnutrition in a new light. Nearly every country in the world is affected by malnutrition, and multiple malnutrition burdens are the "new normal." Unfortunately, the world is off track to meet the 2025 World Health Assembly (WHA) targets for nutrition. Many countries are, however, making good progress on WHA indicators, providing inspiration and guidance for others. Beyond the WHA goals, nutrition needs to be more strongly represented in the Sustainable Development Goal (SDG) framework. At present, it is only explicitly mentioned in 1 of 169 SDG targets despite the many contributions improved nutritional status will make to their attainment. To achieve improvements in nutrition status, it is vital to scale up nutrition programs. We identify bottlenecks in the scale-up of nutrition-specific and nutrition-sensitive approaches and highlight actions to accelerate coverage and reach. Holding stakeholders to account for delivery on nutrition actions requires a well-functioning accountability infrastructure, which is lacking in nutrition. New accountability mechanisms need piloting and evaluation, financial resource flows to nutrition need to be made explicit, nutrition spending targets should be established, and some key data gaps need to be filled. For example, many UN member states cannot report on their WHA progress and those that can often rely on data >5 y old. The world can accelerate malnutrition reduction substantially, but this will require stronger accountability mechanisms to hold all stakeholders to account.